The factors of dysregualtion of the immune response (at different stage of its implementation) in patients with pulmonary tuberculosis - E. G. Churina; O. I. Urazova; V. V. Novitskiy; I. Ye. Yesimova; T. Ye. Kononova; O. V. Filinyuk; Yu. V. Kolobovnikova; A. I. Dmitrieva (Бюллетень сибирской медицины)
The article provides an overview of scientific research to explain the mechanisms of inefficient implementation of antigen-specific immune response in patients with tuberculosis infection depending on the clinical form (infiltrative and disseminated pulmonary tuberculosis) and the course (drug-sensitive and drug-resistant pulmonary tuberculosis) of the disease. The mechanisms of immune imbalance in patients with pulmonary tuberculosis are associated with abnormal co-stimulation of a signal required for the activation of T-lymphocytes and immunosuppressive influence of regulatory T-cells both when they interact with dendritic cells at the inductive stage of the immune response, and in the process of differentiation and proliferation of effector cells with formation of suppressive mode of immune-regulation.